Pemberian Kunyit (Curcuma Longa L.) sebagai alternatif penyembuhan penyakit kanker kulit - Istiqamah, Istiqamah; Mukhidah, Rohma Nurussaniati; Suhari, Ananda Putra; Maulana, Moch Dani; Fauza, Firda (Maliki Interdisciplinary Journal, 2024)
Skin cancer, also known as melanoma, is a cancer disease that has been on the rise over the years in most countries of the world and is most commonly affected by the white population. Skin cancer has symptoms such as Basal Cell Carcinoma (BCC) that occurs in areas of skin that are often exposed to sunlight, such as the skin of the neck or face, shiny and soft bumps on the skin. The study aims to find out the benefits of curcuma (Curcuma longa L.) as an alternative cure for melanoma skin cancer. The results show that the curcumin compounds in the plant Curcuma longa have a role in inhibiting the proliferation of skin cancer disease cells.